Pengaruh Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian pada Furniture di UD Rahayu Klungkung - Putu Gede Denny Herlambang; Ni Ketut Sukanti; Luh Komang Restu Cahyani (Pusat Riset dan Inovasi Nasional, 2025)
Purchasing decision is a process where individuals evaluate many factors and decide to buy a product. Product Quality and Perceived Price are independent variables that influence purchasing decisions. The formulation of the problem in this study is whether product quality and price perceptions partially and simultaneously influence purchasing decisions on furniture at UD. Rahayu Klungkung? The research objective was to determine the effect of product quality and price perceptions partially and simultaneously on purchasing decisions on furniture at UD. Rahayu Klungkung. The population in this study are all consumers who buy furniture products at UD. Rahayu Klungkung. The number of samples was determined by purposive sampling technique, namely as many as 96 respondents. Data were analyzed using the classical assumption test, multiple linear regression analysis, determination analysis, simultaneous significance test (F-test) and partial significance test (t-test). The results showed that product quality has a positive and significant effect partially on purchasing decisions. Perceived price has a positive and significant effect partially on purchasing decisions. Product quality and price perceptions have a positive and significant simultaneous effect on purchasing decisions.